(3eYLe eG GSJYLe ef CSeGA GdHdOGfs - (3YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSj, CHh YHjO,J (B487 (3g` s ((3CMeO Hf eMeO Hf YHO Gddg GdehUdi s)
(3ChdgG (B:s
(3cJGH MQa GdPGd , GdPGd hGdgeRI (B_ (3GdPjHI Ydi daX GdCfKi ef GdPFGH s
(3BNQgG (B:s
(3hdHf , eDfKI GSe ddLHd heG Mhdg dG jLQi , bGd GdQGYi Sjcajc GdEdg heSfeGJ cLfOd dHf JWQO GdUdGdG BNQ cJGH eYL eG GSJYLe s
(3GdfSNI HgG MhGTs
(3HMhGTI GdfSNI ebGHdGJ hJUMjMGJ LjOI cJHgG Ydi Hf eMeO Hf CMeO Hf YHO Gddg Gdjhfjfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B75s
Keywords: (3GdLZQGajG h GdHdOGfs